Sustainable Pedagogical Space: Water Risk Reduction Management Through Permaculture Pedagogy - Simanjuntak, Susi Andriani; Zhou, Yuqin; Li, Si Wen (CSID Journal of Infrastructure Development, 2025)
This study explores a Permaculture design approach to promote water conservation and reduce water dependency, particularly in response to plastic pollution. Permaculture emphasizes water ethics, conservation principles, rainwater harvesting (via tanks, soil, land, and biomass), greywater reuse, and biological remediation techniques for water recycling and purification. The study applies a contextually adapted environmental pedagogy based on Permaculture for primary school students in North Sumatra, Indonesia, focusing on sustainable water conservation and plastic litter risk reduction. A case study method was employed, targeting schools that voluntarily participated. The approach highlights three commonly overlooked dimensions in environmental education: community connection, place-based authenticity, and experience-based learning. Engaging young learners in local environmental monitoring, management, and communication aligns with several Sustainable Development Goals (SDGs), including SDG 3 (Good Health and Well-being), SDG 4 (Quality Education), SDG 8 (Decent Work and Economic Growth), SDG 9 (Industry, Innovation, and Infrastructure), and SDG 14 (Life Below Water). Thematic analysis revealed five key outcomes related to eco-pedagogy and place-based learning: (1) developing critical thinking through connections between past and present marine conditions; (2) identifying the stages of plastic degradation; (3) fostering respect for aquatic life and awareness of plastic waste impacts; (4) understanding local waterway issues from ditches to rivers and cultivating environmental responsibility; and (5) recognizing socio-environmental linkages through reflective activities such as letter-writing to local authorities. Findings emphasize the value of involving young participants in environmental initiatives, particularly those addressing plastic pollution and sustainable resource management. The study also proposes practical pedagogical strategies rooted in Permaculture principles for students, families, schools, and local communities.